SIGNIFIKANSI MAKNA NUSHŪZ DALAM QS. AL-NISĀ[4]: 34 DENGAN TINJAUAN TEORI MA’NĀ-CUM-MAGHZĀ - Dewi Umaroh (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
This paper aimed to explore the significance of the verse of wife's nushūz in QS. al-Nisā'[4]: 34 which was incidentally interpreted based on the patriarchal system. The ma’nā-cummaghzā theory had employed to reinterpret the object. This theory balanced the reading of the literal meaning (al-ma’nā al-aṣlī) and the main message (maghzā). Based on the application of this theory, the results were obtained: first, al-ma‘nā al-tārīkhī of wife's nushūz is an attitude of disobedience or against her wife to her husband. Second, al-maghzā al-tārikhī obtained is that the verse came down in the Medina period which was full of male superiority over women where men were predicated of qawwām based on certain characteristics so that it had implications for the wife's nushūz. Third, al-maghzā almutaḥarrik which is drawn based on al-ma‘nā al-tārīkhī and al-maghzā al-tārikhī is there are three conditions that must be considered in determining the wife's nushūz namely the husband neglects responsibilities, the husband and wife share roles and the husband is fully responsible for the family. The application of the wife's nushūz as stated in QS. al-Nisā'[4]: 34 can only be applied to the second and third conditions and cannot be applied to the first condition.